Excitonic emission of a triply charged quantum dot molecule in a magnetic field - Adames,M. (2006)
We calculate the exciton states of a Quantum Dot (QD) and a Quantum Dot Molecule (QDM) in an exact way for single, double and triply charged excitons without and with an applied external magnetic field. For the case of single quantum dot, we reproduce the experimental results reported in [2]. We also calculate the emission energies for the neutral molecule QDM as function of the barrier width between the two dots and we find that the Coulomb interaction splits the emission spectra in case of QDM. Concerning hybridization the triply charged QDM behaves in the same way as the QD, but showing several anticrossings with the lower Landau level of the continuum.